Enough is Enough: Changing Adult Behaviors To Reduce Disparities In Discipline Referrals Among African American Males in a Rural Middle School - Mckenzie, Demond Wayne (East Carolina University, 2022)
Despite various efforts to reduce disparities in discipline referrals among African American males in schools, the gap continues to persist. African American males are disciplined at a higher rate than any other demographic in the United States. What might be the root cause? Could the perceptions of adults in the classroom be a major contributing factor? Studies indicate implicit bias exists among all beings and can lead to assumptions that result in preconceived/discriminatory actions toward students of color (Gilliam et al., 2016; Okonofua et al., 2016; Skiba et al., 2002). Schools have attempted to combat these injustices by providing trainings and implementing systems to minimize exclusionary discipline practices to some success. In this mixed method study, we facilitated research-based professional learning and provided coaching to support teachers with the implementation of strategies with the intent of changing behaviors and practices in a specific school setting to create a more equitable culture. This study evaluated professional development and its impact on the perceptions of educators toward African American male students as to determine whether they reduced the number of discipline referrals administered at CPS Middle School, a rural school in North Carolina. Ultimately, we determined while some perceptions and attitudes were changed, there was no change in the disparities among the discipline referrals among African American males potentially due to some unforeseen extenuating factors.
Keywords: disparities; adult behaviors; professional development; School discipline--North Carolina; Discrimination in education--North Carolina; African American middle school boys--North Carolina; Rural schools--North Carolina; Teachers--In-service training--North Carolina